Estetika Visual Sampul Album Grup Musik Folk di Indonesia - Syarip Hidayat; Maha Fadillah Rachman (JURNAL RUPA, 2020)
The development of indie music in Indonesia, which continues to create works of music, express their idealism and expression through songs, disseminating it to the general audience of Indonesian music listeners. The role of graphic design is important in make an image and identity of a musical work, especially in a music album. Folk music in various forms in the cover of his album. This questioned how the actual characteristics of a folk music as outlined in the visuals of an album cover. Visual artwork is used as promotional needs, such as in album covers, posters, merchandise. Visual aesthetics on the cover of folk music albums in Indonesia from the results of the analysis of several album cover design works that were released in different years namely Nowhere to Go in 2009, Roekmana's Repertoire in 2013, and Broken Growing Missing Change in 2016. Difference in years this release has different concepts, references, and music. Analysis found in the visual works of folk music album covers features illustrations that illustrate visuals about the story and the contents of the album that differentiate it from other genre music groups that provide visual photos of the personnel or visuals that do not adequately describe the contents of the album. Visual a folk music cover will indirectly describe and tell the music, the contents of the song, as well as the atmosphere that was delivered by the music groups. Keywords: Visual Aesthetics, Folk Music, Album Cover, graphic design